Molecular dynamics simulations of the adsorption of an intrinsically disordered protein: Force field and water model evaluation in comparison with experiments - Koder Hamid, Mona; Månsson, Linda K.; Meklesh, Viktoriia; Persson, Per; Skepö, Marie (Frontiers in Molecular Biosciences, 2022)
The aim of this study is to investigate possible structural changes for an intrinsically disordered protein (IDP) when it adsorbs to a solid surface. Molecular dynamics (MD) simulations is a crucial tool to obtain a more detailed information on the atomistic and molecular level and could be very fruitful in this respect. An evaluation of four different force field and water model combinations have been applied, (A) AMBER99SBN-ILDN + TIP4P-D, (B) CHARM36IDPSFF + TIP4P-D, (C) CHARM36IDPSFF + TIP3P, and (D) CHARMM36m + modified TIP3P. The results have been qualitatively compared with results from spectroscopic techniques such as synchrotron radiation circular dichroism and attenuated total reflectance Fourier transform infrared spectroscopy. The model IDP corresponds to the first 33 amino acids of the N-terminal of magnesium transporter A (MgtA), and is denoted KEIF. With a net charge of +3, KEIF is found to adsorb to the anionic synthetic clay mineral Laponite® with a concomitant release of counterions from the surface, which results in an increase of the entropy. The experimental results show that the peptide is largely disordered with a random coil conformation, whereas upon adsorption, the helical content ($α$- and/or 3$_{10}$-helices) was observed to increase. MD simulations corroborates these findings, and further reveals an increase in polyproline II helices, and an extension of the peptide conformation in the adsorbed state. The simulations provide atomic resolution of the adsorbed ensemble of structures, where the arginine residues had a high propensity to form hydrogen bonds with the surface. This study provides insight into the structural changes of surface-active IDPs induced by adsorption, which may play an important role for their function.